Comparison of alternatives to amplitude thresholding for onset detection of acoustic emission signals - Zhao, Yifan (Cranfield University, 2017)
Data used in the publication "New methods for onset detection of acoustic emission signals".- crack_data 111 pairs: data used for Section 4.- AE data: data used for Section 2.Also used in the paper "Comparison of alternatives to amplitude thresholding for onset detection of acoustic emission signals".
Keywords: 'Onset detection'; 'Acoustic emission'; 'Structural health monitoring'; 'Acoustics and Noise Control (excl. Architectural Acoustics)'